The S-layer homology domain-containing protein SlhA from Paenibacillus alvei CCM 2051(T) is important for swarming and biofilm formation. - Bettina Janesch; Andrea Koerdt; Paul Messner; Christina Schäffer (PLoS ONE)
Background Swarming and biofilm formation have been studied for a variety of bacteria. While this is well investigated for Gram-negative bacteria, less is known about Gram-positive bacteria, including Paenibacillus alvei, a secondary invader of diseased honeybee colonies infected with Melissococcus pluton, the causative agent of European foulbrood (EFB). Methodology Paenibacillus alvei CCM 2051(T) is a Gram-positive bacterium which was recently shown to employ S-layer homology (SLH) domains as cell wall targeting modules to display proteins on its cell surface. This study deals with the newly identified 1335-amino acid protein SlhA from P. alvei which carries at the C‑terminus three consecutive SLH-motifs containing the predicted binding sequences SRGE, VRQD, and LRGD instead of the common TRAE motif. Based on the proof of cell surface location of SlhA by fluorescence microscopy using a SlhA-GFP chimera, the binding mechanism was investigated in an in vitro assay. To unravel a putative function of the SlhA protein, a knockout mutant was constructed. Experimental data indicated that one SLH domain is sufficient for anchoring of SlhA to the cell surface, and the SLH domains of SlhA recognize both the peptidoglycan and the secondary cell wall polymer in vitro. This is in agreement with previous data from the S-layer protein SpaA, pinpointing a wider utilization of that mechanism for cell surface display of proteins in P. alvei. Compared to the wild-type bacterium ΔslhA revealed changed colony morphology, loss of swarming motility and impaired biofilm formation. The phenotype was similar to that of the flagella knockout Δhag, possibly due to reduced EPS production influencing the functionality of the flagella of ΔslhA. Conclusion This study demonstrates the involvement of the SLH domain-containing protein SlhA in swarming and biofilm formation of P. alvei CCM 2051(T).